The Efektivitas Perilaku Cerdik dan Patuh untuk Mencegah Stroke Berulang - Fransiska Anita Ekawati; Yunita Carolina; Sr. Anita Sampe; SJMJ, Felisima Ganut (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; the impact of repeated strokes is heavier because it increases mortality and disability which adds to the economic burden, decreasing the quality of life of post-stroke patients. Aim; know the effectiveness of providing health education about a CERDIK and PATUH lifestyle in preventing recurrent strokes. Method; This type of research is a quasi-experimental pre and post-test without control. Test using Wilcoxon. Result; shows that there is an effect of education on the behavior of stroke sufferers in preventing recurrent stroke attacks and there is an effect of education on the prevention of the risk of recurrent stroke. Conclusion; There is an effect of providing education on a healthy lifestyle, BE AWARE, and MODIFY to prevent recurrent strokes on the behavior of stroke sufferers and the risk of recurrent stroke events